Peningkatan dan Determinan Kadar Hemoglobin pada Ibu Hamil Anemia setelah Edukasi dan Konsumsi Kurma di Puskesmas - Jumiati Jumiati; Ika Apriyanti; Titis Wahyuni (Universitas Faletehan, 2026)
Anemia during pregnancy remains a significant health problem that may increase the risk of complications for both mothers and fetuses. Date fruit consumption, as a source of iron and nutrients that support hemoglobin (Hb) synthesis, is considered a potential non-pharmacological intervention to improve Hb levels. This study aimed to analyze the determinants of hemoglobin improvement among pregnant women with anemia following date fruit consumption education at Pamarayan Primary Health Center. This study employed a quasi-experimental design with a one-group pretest-posttest approach involving 48 pregnant women with anemia. The intervention consisted of educational sessions using leaflets accompanied by the consumption of five dates per day for 30 days. The Shapiro-Wilk test indicated that Hb data were not normally distributed; therefore, changes in Hb levels were analyzed using the Wilcoxon signed-rank test, while factors influencing Hb improvement were analyzed using chi square. Hb level increased significantly from 8.8 g/dL to 11.2 g/dL (p<0.001). Parity, educational level, occupation, nutritional status, adherence to iron tablet supplementation, and the frequency of antenatal care (ANC) visits were significantly associated with Hb improvement (p<0.05). Optimizing antenatal care services is essential to support the prevention and management of anemia during pregnancy.